Penalisations of Brownian motion with its maximum and minimum processes as weak forms of Skorokhod embedding - Roynette, B.; Vallois, P.; Yor, M. (Інститут математики НАН України, 2008)
We develop a Brownian penalisation procedure related to weight processes (Ft) of the type: Ft := f(It, St) where f is a bounded function with compact support and St (resp. It) is the one-sided maximum (resp. minimum) of the Brownian motion up to time t. Two main cases are treated: either Ft is the indicator function of {It ≥ α, St ≤ β} or Ft is null when {St − It > c} for some c > 0. Then we apply these results to some kind of asymptotic Skorokhod embedding problem.